2016
DOI: 10.1186/s12875-016-0407-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring interprofessional collaboration during the integration of diabetes teams into primary care

Abstract: BackgroundSpecialised diabetes teams, specifically certified nurse and dietitian diabetes educator teams, are being integrated part-time into primary care to provide better care and support for Canadians living with diabetes.This practice model is being implemented throughout Canada in an effort to increase patient access to diabetes education, self-management training, and support. Interprofessional collaboration can have positive effects on both health processes and patient health outcomes, but few studies h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 46 publications
1
51
0
12
Order By: Relevance
“…20,21 According to the American Academy of Pediatrics’s (AAP) policy statement on substance use, pediatricians are recommended to screen all adolescents for substance use behaviors and provide brief advice and appropriate referrals based on the indicated risk level as part of routine care. 22 Similarly, screening and prevention of obesity through promoting healthy eating patterns and encouraging increased physical activity are recommended by both the Society for Adolescent Health and Medicine (SAHM) and the AAP.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 According to the American Academy of Pediatrics’s (AAP) policy statement on substance use, pediatricians are recommended to screen all adolescents for substance use behaviors and provide brief advice and appropriate referrals based on the indicated risk level as part of routine care. 22 Similarly, screening and prevention of obesity through promoting healthy eating patterns and encouraging increased physical activity are recommended by both the Society for Adolescent Health and Medicine (SAHM) and the AAP.…”
Section: Introductionmentioning
confidence: 99%
“…Similar experiences have been reported elsewhere. A Canadian study that explored interprofessional collaboration in diabetes care found poor interaction between dieticians, diabetes educators and nurses caused by overlapping or shared role boundaries (Gucciardi, Espin, Morganti, & Dorado, 2016). This situation appeared to strongly influence the attitudes of the nurses towards diabetes care and patient education, which may also be the case not only in Saudi Arabia but in other parts of the world (Dubois & Singh, 2009;Eijkelberg, Spreeuwenberg, Wolffenbuttel, van Wilderen, & Mur-Veeman, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Having specific skills is necessary to complement each other's roles (Gucciardi et al. ) and to improve diabetes care (Ugur et al. ).…”
Section: Discussionmentioning
confidence: 99%